Evaluating University Teacher’s Perception about e-teaching During Pandemic in the Higher Educational Institutes of Pakistan - Muhammad Asif Nadeem, Zaib u Nisa, (PJDOL, 2023)
The objective of the research was to identify teacher’s readiness towards the acceptance of technology assessment model in e-teaching and identification of the problems faced by the teachers while switching to e-teaching. The nature of the study was qualitative. Data was collected from 04 public sector universities. Purposive sampling technique was used to select the group of the study. Sample consisted of the teachers (male and female) teaching in the teacher training institutes of southern Punjab (Pakistan). 20 teachers from various universities were selected for the interview. Research tool used for the data collection of the study was structure interview.